Identification and differentiation of isolates of Colletotrichum gloeosporioides from yam by random amplified polymorphic DNA markers - Thottappilly, G.; Mignouna, Hodeba D.; Onasanya, A.; Abang, Mathew M.; Oyelakin, O.; Singh, N.K. (1999)
DNA was extracted from the mycelia of Colletotrichum gloeosporioides[Glomerella cingulata] isolates from yam, and amplification reactions using 11 random primers generated 116 DNA bands, 70 of them being informative. The electrophoretic patterns revealed by these primers allowed the identification of distinct morphotypes and virulence phenotypes, and the determination of the genetic distances between different isolates. 51 isolates of C. gloeosporioides, previously characterised on the basis of morphology and virulence, were classified into 4 groups following RAPD analysis. Two slow-growing orange (SGO) isolates from yam tubers could be differentiated from isolates obtained from leaves and botanic seeds of yam. The weakly virulent fast growing grey (FGG) isolates, were different from the aggressive slow-growing grey (SGG) isolates while the fast growing salmon (FGS) isolates were very heterogeneous at DNA level. No correlation was found between classification by RAPD and rate of growth of isolates, in culture or geographic origin. Undoubtedly, DNA-based molecular markers represent a potent tool for the identification of distinct populations of C. gloeosporioides and thus the development of D. alata cultivars with stable genetic resistance to anthracnose.